4-Hydroxy-2-nonenal: a critical target in oxidative stress? - Breitzig, Mason (Am J Physiol Cell Physiol, 2016)
In this perspective, we summarize and discuss critical advancements in the study of 4-hydroxy-2-nonenal (4-HNE) as it relates to diseases and clinical complications either caused or exacerbated by oxidative stress. Since its identification in 1980, 4-HNE has been extensively studied with an emphasis on its formation, its role in pathology, and its targets. As a reactive aldehyde, and a product of lipid peroxidation, studies corroborate its ability to disrupt signal transduction and protein activity, as well as induce inflammation and trigger cellular apoptosis in conditions of oxidative stress. Notably, we discuss the role of natural enzymes involved in the regulation of 4-HNE, and how they can be applied to its detoxification in various physiological conditions.